Driving Digital Value in Healthcare: The Mediating Role of Intention to Use in the Relationship Between System Factors and Net Benefit Among Users of the Hospital Information System (HIS) in the Medical Check-Up Unit XY Private Hospital Indonesia 2025 - Indri Rengganis Budi Utomo; Munawar Munawar; Ratna Indrawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study was grounded on observations indicating that the utilization rate of the Hospital Information Management System (HIS) WPRO at the Medical Check-Up (MCU) Unit of XY Hospital remains relatively low. The purpose of this research is to analyze the influence of Information Quality, System Quality, Facilitating Conditions, Subjective Norm, and Intention to Use on the Net Benefit of HIS usage at the MCU Unit of XY Hospital, employing a modified DeLone & McLean Information System Success Model. This study used a quantitative approach with a causal design. The study population consisted of all hospital staff involved in the Medical Check-Up (MCU) services, totaling 84 respondents. Sampling was carried out using a probability sampling method with a saturated sample, as all eligible MCU personnel were included in the study. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results demonstrate that Information Quality, System Quality, Facilitating Conditions, Subjective Norm, and Intention to Use simultaneously exert a significant influence on the Net Benefit of HIS utilization (p < 0.05). Theoretically, these findings support the propositions of prior research and confirm the relevance of established IS success models. From a managerial perspective, the results provide practical recommendations for XY Hospital to enhance HIS implementation by improving data integration, strengthening information security protocols, and increasing organizational support. These initiatives are expected to foster stronger user intention and, ultimately, lead to greater tangible benefits from HIS implementation in healthcare operations.